Nutrition and prevention of Alzheimer’s dementia - Swaminathan, Arun; Jicha, Gregory A. (Frontiers in Aging Neuroscience, 2014)
A nutritional approach to prevent, slow, or halt the progression of disease is a promising strategy that has been widely investigated. Much epidemiologic data suggests that nutritional intake may influence the development and progression of Alzheimer’s dementia (AD). Modifiable, environmental causes of AD include potential metabolic derangements caused by dietary insufficiency and or excess that may be corrected by nutritional supplementation and or dietary modification. Many nutritional supplements contain a myriad of health promoting constituents (anti-oxidants, vitamins, trace minerals, flavonoids, lipids, …etc.) that may have novel mechanisms of action affecting cellular health and regeneration, the aging process itself, or may specifically disrupt pathogenic pathways in the development of AD. Nutritional modifications have the advantage of being cost effective, easy to implement, socially acceptable and generally safe and devoid of significant adverse events in most cases. Many nutritional interventions have been studied and continue to be evaluated in hopes of finding a successful agent, combination of agents, or dietary modifications that can be used for the prevention and or treatment of AD. The current review focuses on several key nutritional compounds and dietary modifications that have been studied in humans, and further discusses the rationale underlying their potential utility for the prevention and treatment of AD.